Aplikasi Mesin Pemasak Minuman Rempah Jahe (Zingiber officinale) Dengan Pengaduk Otomatis di UKM Polanmadu - Choiroel Anam; Nindyah Widyamurti; Danar Praseptiangga; Anastriyani Yulviatun; Dwi Aries Himawanto (Universitas Sebelas Maret, 2021)
Cooking Machine Application of Ginger Drink (Zingiber officinale) with Automatic Stirrer at UKM Polanmadu. The trend of instant spice drinks that function to maintain the body’s immunity is growing rapidly in the era of the Covid-19 pandemic. Ginger, which is a spice with various benefits, has made many Small and Medium Enterprises (SMEs) industry players take advantage of this potential. One of them is the instant spice drink SME industry player